PEDAGOGICAL POTENTIAL OF THE ARTS COMPLEX IN THE PROCESS OF THE FORMATION OF AESTHETIC PERCEPTION OF JUNIOR PUPILS - Brovchak, Liudmyla; Starovoit, Lesia; Likhitska, Larysa; Todosienko, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the research are illuminated the following subjects: the topical issue of the aesthetic development of junior pupil's personality, search for new approaches to children's education and development and their implementation to the educational process of the modern school, maximal use of pupil's creative potential in the elementary school, the formation and development of the aesthetic sense of reality, the aesthetic attitude to the surrounding world, to the nature, to the arts and applying the principle of different art forms correlation.The use of the art at the lessons of the art cycle at establishments of primary education and approaches, which have been proposed by us, analysis of findings of experimental data allows to assume that the development of aesthetic feelings, tastes, ideals, artistic skills, competences in the sphere of art, should be an undetectable condition of the educational subjects of primary school, especially of the art cycle.We detected the growth of the level of aesthetic perception which is connected with the development of emotional and sensitive sphere and artistic potential of junior school children, that is determined by results of applying of the proposed approach to activation of aesthetic perception of junior school-age children through the art at the lessons of the art cycle. It also determines positive changes in the tendency of humanization and the aestheticization of the educational process.